Outbreak of Alimentary Tick-Borne Encephalitis in Eastern Slovakia: An Analysis of Affected Patients and Long-Term Outcomes - Zuzana Paraličová; Jakub Sekula; Pavol Jarčuška; Martin Novotný; Alena Rovňáková; Ján Hockicko; Ivana Hockicková (Pathogens, 2022)
Objective: Tick-borne encephalitis (TBE) is an endemic zoonotic viral disease in many European countries and in the central and eastern parts of Asia. Slovakia reports the highest occurrence of alimentary tick-borne encephalitis in Europe, after the consumption of unpasteurized milk and cheese from domestic ruminants. In May 2016, an outbreak of tick-borne encephalitis that emerged after the consumption of sheep cheese occurred in eastern Slovakia. In total, 44 people were ill and 36 were hospitalized. Methods: Data from the 36 hospitalized patients at the Department of Infectology and Travel Medicine in Košice with TBE were retrospectively analysed from the medical documentation. The patients were contacted 3 years after discharge. Results: Twenty of the hospitalized patients had meningoencephalitis and 16 had meningitis. The main symptoms that occurred in all patients were fever and headache. Nuchal rigidity was seen in 50% of the patients. Three patients developed late systemic complications and another six patients had psychiatric complications. None of the patients died. Three years after the disease onset, 52% of contacted patients reported persistent discomfort. Conclusions: TBE is an infection with a wide range of clinical courses. Our findings suggest that alimentary-acquired TBE lead to severe disease and persistent discomfort.